2019
DOI: 10.1093/glycob/cwz096
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of hepatocyte sialylation drives spontaneous fatty liver disease and inflammation

Abstract: Circulatory protein glycosylation is a biomarker of multiple disease and inflammatory states and has been applied in the clinic for liver dysfunction, heart disease and diabetes. With the notable exception of antibodies, the liver produces most of the circulatory glycoproteins, including the acute phase proteins released as a function of the inflammatory response. Among these proteins is β-galactoside α2,6-sialyltransferase (ST6Gal1), an enzyme required for α2,6-linked sialylation of glycoproteins. Here, we de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 64 publications
1
22
0
Order By: Relevance
“…Interestingly, an agedependent autoimmune phenotype was also observed in mice lacking other endogenous lectins including Siglec-G, a sialic acidbinding lectin, deficiency of which led to elevated autoantibody levels and mild glomerulonephritis (53), and Gal3, absence of which led to a lupus-like disease by promoting spontaneous germinal center formation and autoantibody production (54). Furthermore, loss of liver α2,6-sialyltransferase (ST6Gal1), an enzyme required for α2,6-linked sialylation which prevents Gal1 binding, elicits fatty liver disease characterized by age-dependent buildup of fatty acid droplets and a proinflammatory phenotype involving polarization of M1-type macrophages (55). Altogether, these observations suggest a broader role of endogenous glycan-binding proteins and their glycosylated ligands in supporting immune tolerance in the context of immunological senescence.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, an agedependent autoimmune phenotype was also observed in mice lacking other endogenous lectins including Siglec-G, a sialic acidbinding lectin, deficiency of which led to elevated autoantibody levels and mild glomerulonephritis (53), and Gal3, absence of which led to a lupus-like disease by promoting spontaneous germinal center formation and autoantibody production (54). Furthermore, loss of liver α2,6-sialyltransferase (ST6Gal1), an enzyme required for α2,6-linked sialylation which prevents Gal1 binding, elicits fatty liver disease characterized by age-dependent buildup of fatty acid droplets and a proinflammatory phenotype involving polarization of M1-type macrophages (55). Altogether, these observations suggest a broader role of endogenous glycan-binding proteins and their glycosylated ligands in supporting immune tolerance in the context of immunological senescence.…”
Section: Discussionmentioning
confidence: 99%
“…We have also highlighted a number of other selected genes that may drive changes within atherosclerotic plaques in PWH (see Highlighted Genes, Fig 5). For example, the gene for ST6 β-galactoside α-2,6-sialyltransferase1 (ST6GAL1) is associated with increased fat droplet formation, inflammatory cytokine expression and promotion of a pro-inflammatory M1 macrophage phenotype in mouse models [52]. Pituitary Tumor-Transforming gene 1 (PTTG1) was also significantly correlated with lipid levels in PWH and regulates myeloid cell differentiation [53].…”
Section: Systems Model Of Mdm Phenotype In Pwhmentioning
confidence: 99%
“…For example, increased cigarette smoke exposure was shown to alter sialylation of the fallopian tubes potentially through ST6GAL1 in ectopic pregnancy ( 40 ). In addition, changes in protein sialylation were shown to contribute to fatty liver deposition and various inflammatory responses ( 45 ). Our findings demonstrate that loss of ST6GAL1 or exposure to cigarette smoke leads to decreased sialylation ( Figures 1 , 2 ) and increased IL-6 expression/secretion in bronchial epithelial cells ( Figures 3 , 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…BACE1 expression has been shown to affect the sialylation of soluble/cell surface glycoproteins through cleavage of ST6GAL1 ( 52 ) suggesting that the soluble form of the ST6GAL1 still has activity when released [others have shown that ST6GAL1 has activity in a secreted/soluble form ( 53 )]. Additionally, secreted/circulating ST6GAL1 has been associated with inflammation ( 45 , 54 , 55 ). Here, we show that inhibition of BACE1 reduced ST6GAL1 secretion and α2-6 sialylation and resulted in augmented IL-6 secretion in HBECs similar to that found with CSE treatment ( Figure 5 ).…”
Section: Discussionmentioning
confidence: 99%